Analisis Hukum Penyelesaian Sengketa Kepailitan Syariah di indonesia - Mona Wulandari; Saifullah Basri (Universitas Batanghari Jambi, 2022)
After the issuance of the Constitutional Court Decision Number 093/PUU-X/2012, the quo vadis regarding the dualism of the authority to settle sharia economic disputes has ended. The Religious Courts are legally constitutional as the only institution authorized to resolve sharia economic disputes through litigation. However, this authority is not fully implemented, there are still other sharia economic disputes whose resolution is decided by the Commercial Court within the scope of the General Courts, namely bankruptcy disputes and PKPU (Debt Payment Obligations Suspension) in Islamic financial institutions. So after the decision of the Constitutional Court Number 93/PUU-X/2012, the litigation resolution of sharia banking disputes is handled by the Religious Courts, while non-litigation is handled by arbitration and other alternative dispute resolutions. Arbitration in this case is the National Sharia Arbitration Board (BASYARNAS) while other alternative dispute resolutions are resolved through dispute resolution agreements based on good faith.